Psychological Skills and "the Paras": The Indirect Effects of Psychological Skills on Endurance. Issue 4 (2nd October 2017) - Arthur, Rosemary Anne; Fitzwater, James; Roberts, Ross; Hardy, James; Arthur, Calum Alexander
Abstract : We examined the indirect effects of basic psychological skills (PS) on military endurance through enhanced advanced PS while controlling for fitness. British Army recruits ( n = 159) participated in three endurance events for Parachute Regiment selection and completed an adapted Test of Performance Strategies questionnaire (Hardy et al., 2010 ). Following confirmatory factor analyses, the multiple mediation regression analyses using PROCESS (Hayes, 2013 ) suggested that goal setting, imagery and relaxation all had positive indirect effects on endurance via activation, with goal setting also impacting on endurance via negative thinking. These data provide some support for basic PS influencing endurance via advanced PS.